2018
DOI: 10.3390/s18124455
|View full text |Cite
|
Sign up to set email alerts
|

Dressing Tool Condition Monitoring through Impedance-Based Sensors: Part 1—PZT Diaphragm Transducer Response and EMI Sensing Technique

Abstract: Low-cost piezoelectric lead zirconate titanate (PZT) diaphragm transducers have attracted increasing attention as effective sensing devices, based on the electromechanical impedance (EMI) principle, for applications in many engineering sectors. Due to the considerable potential of PZT diaphragm transducers in terms of excellent electromechanical coupling properties, low implementation cost and wide-band frequency response, this technique provides a new alternative approach for tool condition monitoring in grin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…An industrial single-point dresser of a natural diamond was used for the dressing operation. The experiment was conducted following the approaches reported by references [4,9,15,16]. Each trial consisted of single dressing passes (grinding wheel and dresser diamond tip interface).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…An industrial single-point dresser of a natural diamond was used for the dressing operation. The experiment was conducted following the approaches reported by references [4,9,15,16]. Each trial consisted of single dressing passes (grinding wheel and dresser diamond tip interface).…”
Section: Methodsmentioning
confidence: 99%
“…The diamond's worn area was measured using computer-aided design (CAD) software. Figure 1 shows the experimental setup and the DAQ system used in the present study, based on the approach reported in [9]. As a transducer, a low-cost PZT piezoelectric diaphragm, model 7BB-20-6, from MURATA Inc. (Smyrna, GA, USA), was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ceramic is coated with a thin metallic film (usually silver) that acts as an electrode [12]. The PZT diaphragms can operate in both active and passive configurations and have an average cost of a few cents versus the high average cost of AE sensors, which range from hundreds to thousands of dollars [18]. In addition, they are compact, flexible, lightweight and simple acoustic components widely used in various electronic devices to produce sound (alarm, ringing and beep) [12,19].…”
Section: Traditional Monitoring Techniques Applied To Industrial Pmentioning
confidence: 99%